Ceramide in Cystic Fibrosis: A Potential New Target for Therapeutic Intervention. (24th November 2010) - Wojewodka, Gabriella; De Sanctis, Juan B.; Radzioch, Danuta
Abstract : Patients with cystic fibrosis (CF) are afflicted with many symptoms but the greatest challenge is the fight against chronic bacterial infections, leading to decreased lung function and ultimately death. Our group has recently found reduced levels of ceramides in CF patients and mice. Ceramides are sphingolipids involved in the structure of cell membranes but also participate in the inflammatory response, in cell signalling through membrane microdomains (lipid rafts), and in apoptosis. These characteristics of ceramides make them strong candidates for therapeutic intervention in CF. As more studies have come to evaluate the role of ceramide in CF, conflicting results have been described. This paper discusses various views regarding the potential role of ceramide in CF, summarizes methods of ceramide detection and their role in the regulation of cellular and molecular processes.